Penerapan Diabetes Self Management Education (DSME) dalam Meningkatkan Self Care Penderita Diabetes Melitus - Yureya Nita; Angga Arfina; Yeni Devita; Stephanie Dwiguna (LPPM Universitas Bumigora, 2021)
Diabetes mellitus (DM) is a chronic disease that occurs due to the body's inability to carry out the metabolism of carbohydrates, fats and proteins due to an insulin defect. DM is progressive, this will cause the patient to experience hyperglycemia which can increase glucose levels in the blood. In 2015, there were about 415 million adults with diabetes. This service activity is expected to provide information about educational programs for DM sufferers and involve their families to prevent further complications, as well as increase independence in self-care and quality of life for DM sufferers. The method of implementing this service is by checking vital signs, measuring blood sugar, providing health education about DM and evaluating with an education method based on DSME (Diabetes Self Management Education). This activity was attended by 17 participants in the first and second activities and 15 people in the third activity. The results of this service were attended by most of the participants having blood sugar levels when they were above normal (> 140 mg/dL), which was in accordance with the target of the participants and went quite well. Overall self-management education activities to improve self-care for DM patients can be said to be successful